Findings From a Two-Year Effectiveness Trial of the Science Notebook in a Universal Design for Learning Environment - Yu, Jennifer; Wei, Xin; Hall, Tracey E.; Oehlkers, Agatha; Ferguson, Kate; Robinson, Kristin H.; Blackorby, Jose (Frontiers in Education, 2021)
This cluster randomized control trial examines the effects of the Science Notebook in a Universal Design for Learning Environment (SNUDLE) on elementary school student science academic achievement and motivation outcomes. Multilevel analyses examined the impact of SNUDLE for all students and important student subgroups. Overall, students who received the SNUDLE intervention had similar motivation and academic achievement in science to their peers who did not receive the SNUDLE intervention. However, relative to students with disabilities in the comparison group, students with disabilities who used SNUDLE scored significantly higher on motivation in science and science academic achievement, with effect sizes (ES) ranging from 0.82 to 1.01. Furthermore, SNUDLE appeared to have a small but statistically significant positive impact on science academic performance among students whose home language is other than English or Spanish with an ES of 0.35. Fidelity of implementation analysis shows sufficient teacher training but fidelity of teacher and student usage of SNUDLE needs to be improved. The qualitative analysis of teacher interviews suggests that teachers perceived benefits of SNUDLE in support language acquisition and science writing skills. These Both quantitative and qualitative findings suggest that SNUDLE holds promise for improving academic performance in science and confidence and motivation among some of the most vulnerable student populations.